DESAIN BIOBALL BERBAHAN KOMPOSIT BULU AYAM-RESIN POLYESTER: SIFAT MATERIAL, KARAKTERISTIK BENTUK DAN KARAKTERISTIK HIDRAULIK - Ruslim Budianto; Agus Prasetya; Mudjijana - (Master in Systems Engineering, 2013)
Chicken Feather is main waste product of chicken processing as food, however it has a good potential for used in composite material. Material stiffness increase caused by hydrophobic Keratin which is contained in chicken feather both feather quill and feather fiber. Composite material as biofilter media potentially used to improve effectively of septic tank. The study was conducted to determine the effect of chicken feather fiber adding on density, impact strength and flexural strength of polyester composite, with addition of 10%, 15%, 20%, and 25% of feather fiber as variable. The best composition by mechanical test applied as biofilter material (bioball). Bioball characteristic was investigated to give some parameters used in wastewater treatment design, such as porosity of media, specific surface area, and density of bed media, spherical factor and biomass accumulation capacity. The parameters investigated in each bioball media with wide of bioball’s wall gap are 2 mm, 3 mm and 4 mm as variable. Chicken feather fiber composite has been used as bioball material provided light material 1,124 gr/cm3 in density. Increase in material strength was obtained by adding chicken feather fiber, bioball have been made has 44.291 MPa in maximum flexural strength and 5,781 kJ/cm2 in maximum impact strength. Bioball which has casted 5 cm in diameter, divided into three of types; bioball 2 (wall space 2 mm), bioball 3 (wall space 3 mm) and bioball 4 (wall space 4 mm). Bioball have been made has 260-369 cm2/cm3 of specific surface are and 0.78-0.83 of porosity. Based on spherical factor calculation bioball was more similar to parallel plate than rounded shape. Overall the shape was not rounded with spherical factor value between 0.23-0.358. Bioball 2 has the highest biomass capacity. Based on the test, biomass accumulation capacity of bioball 2 was up to 7.0 kg/m3 with estimation of backwashing time is every 20 hours.